Experimental and numerical assessment of masonry walls with new openings strengthened with steel frame - Vera, M. Y. O. (2019)
The creation of new openings in masonry walls is a frequent intervention executed in existing buildings of unreinforced masonry composed of clay bricks. These openings are widely seen at the street-level, where spaces are modified to create new windows or doors for new stores, garages or offices. Depending on their size and position, these interventions may cause significant decrease of the wall’s original in-plane strength and stiffness, thus, compromising the building seismic resistance. For example, when several garages are created, one after another, the risk of inducing the soft-story mechanism, when earthquake forces arrive, increases. Another example is when a door of significant size is introduced in an originally solid masonry wall, which was a key object to guarantee the box-like behavior of the structure. The opening would reduce the cross section of the remaining piers and spandrel, and thus, weaken the wall’s seismic strength. These changes in the original wall have consequences in the box-like behavior, as during earthquake events, the load demands on the remaining shear walls might be larger than their shear capacity. Therefore, strengthening techniques must restore as much as possible the loss of stiffness and strength. Besides, for masonry structures, the technique must be reversible and respect the compatibility between materials, particularly in the case of protected assets. In an attempt to complying with these requirements, engineering practitioner often introduce steel profiles forming a frame inside the opening. Steel is usually preferred because of its high level of reversibility and the stiffness and strength it can provide to masonry without substantially increasing the building self-weight. The design of this steel frame and the stiffness of the masonry wall with opening is based in the available analytical tools, i.e., the Timoshenko Beam Theory. From these calculations, the loss of stiffness when passing from a solid wall to a perforated wall is about 75% for cantilever boundary conditions and 55% for double-fixed. Thus, very stiff profiles for the steel frame are required. In theory, these profiles are capable of fully restoring the stiffness and resistance. The present work is dedicated to evaluate the effectiveness of this steel frame technique by means of experimental and numerical methods. The experimental program was designed to provide full assessment of the effects of introducing a new door opening in brick masonry walls, from the perforation process to the application of in-plane cyclic loads . A flexible steel frame was designed using numerical tools and consisted in four profiles welded together and tied to the surrounding masonry wall by means of dry-driven dowels. The numerical model was validated against the experimental results, and show that neither a very stiff steel frame nor a more flexible one is capable of restoring the original solid wall’s stiffness. However, both are capable of restoring the in-plane strength and ductility. This paper, also shows that using a very stiff profile might lead to a rather brittle response of the reinforced wall, as the masonry starts cracking before activating the frame. This would not happen with a more flexible profile